2019
DOI: 10.31015/jaefs.2019.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of tomato blossom and flower drop to the influence of environmental phenomena (solanum lycopersicum L.)

Abstract: Tomato (Solanum lycopersicum L.) is an important vegetable crop. At present, about 160 million tons of fresh tomatoes are the production from 4.7 million hectares in India (FAOSTAT, 2011). S. lycopersicum are native to South America but were brought to Europe sometime in the 15th century, where they soon became popular and were exported around the world. Pollination is an important ecological interaction and the first step for the sexual reproduction of most plant species (Murcia, 1996). The ecosystem service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been reported that drought stress during the vegetative period can prime plants to subsequent water stress without lowering yield 33 . Conversely, drought episodes at the plant flowering stage can lead to flower abscission due to defects on gynoecium development as well as hormonal impairment and signalling, 34,35 with a consequent reduction in berry yield 35,36 . We estimated the effects of water deprivation at three stages of plant development by quantifying the number of floral buds, flowers and fruits in stressed/recovered plants in respect to plants regarded as well‐watered plants (Control).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that drought stress during the vegetative period can prime plants to subsequent water stress without lowering yield 33 . Conversely, drought episodes at the plant flowering stage can lead to flower abscission due to defects on gynoecium development as well as hormonal impairment and signalling, 34,35 with a consequent reduction in berry yield 35,36 . We estimated the effects of water deprivation at three stages of plant development by quantifying the number of floral buds, flowers and fruits in stressed/recovered plants in respect to plants regarded as well‐watered plants (Control).…”
Section: Resultsmentioning
confidence: 99%